TRP channels and monoterpenes: Past and current leads on analgesic properties - Petitjean, Hugues; Héberlé, Eléa; Hilfiger, Louis; Łapieś, Olga; Rodrigue, Guillaume; Charlet, Alexandre (Frontiers in Molecular Neuroscience, 2022)
The activation of the transient receptor potential (TRP) channels expressed by sensory neurons is essential to the transduction of thermal and mechanical sensory information. In the setting of chronic inflammatory conditions, the activation of the melastatin family member 8 (TRPM8), the TRP vanilloid 1 (TRPV1) and the TRP ankyrin 1 (TRPA1) are correlated with pain hypersensitivity reactions. Monoterpenes, among which pulegone and menthol, a major class of phytocompounds present in essential oils of medicinal plants, are known modulators of those TRP channels activity. In the present review, we correlate monoterpene content of plants with their historical therapeutic properties. We then describe how monoterpenes exert their anti-inflammatory and anti-hyperalgesia through modulation of TRP channels activity. Finally, we discuss the importance and the potential of characterizing new plant extracts, and reassessing studied plant extracts for the development of ethnopharmacology-based innovative treatments for chronic pain. This review suggests that monoterpene solutions, based on composition from traditional healing herbs, offer an interesting avenue for the development of new phytotherapeutic treatments in order to alleviate chronic inflammatory pain condition.